Seismic Vulnerability Assessment of High-Speed Railway Bridges Using Fragility Curves and Considering Soil-Structure Interaction - Bakhtiari Parham; Bargi Khosro (Civil and Environmental Engineering, 2020)
The assessment of the seismic behavior of the high-speed railway bridges is necessary because of the strategic essence of these structures. Evaluating and predicting damages of the bridges that originated by earthquakes with various intensities can provide useful information, which is very helpful in the management of the possible crises. One of the most useful mechanisms for estimating earthquake damages to these bridges is the development of fragility curves for them. Studies on the production of fragility curves on the high-speed railway bridges are limited. In this research, the fragility curve is plotted for two high-speed railway bridges with different pier heights. Due to the differences in the height of these bridges, a comparison of the performance of these structures is also shown. The model of the high-speed railway bridge was created for each model separately in the SeismoStruct software. The soil-structure interaction is also modeled as springs, and its effects are considered. Nonlinear models are also used to model concrete and steel materials. Then, the incremental dynamic analysis was performed under different ground motion records. By using the obtained data from the analysis, appropriate damage states were selected, and finally, the fragility curves were plotted for different performance limit states. The results showed that with increasing pier height, the damage index was raised and for a constant probability of exceedance, the taller pier is demanded a lower spectral acceleration to achieve a performance level.